ASUHAN KEPERAWATAN IBU NIFAS PADA NY F POST SECTIO CAESAREA DI RUANG TERATAI RSUD BATARA SIANG PANGKEP - Sakriawati Sakriawati; Antonio Dwi Saputra Jamon (Public Health And Medicine Journal, 2024)
Sectio Caesarea is a medical action that is needed to help deliveries that cannot be carried out normally due to problems with the mother's health or the condition of the fetus, this problem can be overcome by the role of nurses in providing comprehensive nursing care. The purpose of this study is to be able to carry out nursing care for postpartum mothers with post-sectio caesarean section at Batara Siang Pangkep Hospital.The research method is a qualitative method with a case study approach.The results of the study were obtained in patients with post section caesarea pathological indications that need to be considered is the assessment on physical examination, namely breast enlargement, uterine contractions are good/hard, there is lochia rubra. some changes in physical, psychological and social problems. The nursing problems found in the case review were acute pain, knowledge deficit, risk of infection.the intervention still refers to the target, outcome criteria and time criteria. At the end of the evaluation all objectives can be achieved due to good cooperation between the patient, family and health team, suggestions the involvement of the patient, family and health team that is well established needs to be improved so that mutual trust arises